Viscosity Assessment for Quantifying Engine Oil Deterioration Using New Cost-effective and Handy Fluid Property Sensor - Harish M. Shinde, Anand K. Bewoor (International Journal of Advanced Science and Technology, 2020)
In order to resolve the optimal gap between oil replacement, it is crucial to evaluate the deterioration level of engine oil. Multiple parameters like oxidation, nitration, viscosity and so on are brought into use. Further, to predict percentage engine oil deterioration one of the crucial parameters is viscosity. As, Viscosity measurement by viscometer needs more time to quantify deterioration level in terms change in viscosity. Hence it is a basic motivation for this research work to measure viscosity of deteriorated engine oil samples with a handy setup. For this research work, we collected random samples of use various intervals from service stations that were specifically authorized. We have compared results obtained using standard laboratory setup as per-ASTM D7042 (‘SVM 3000’ Stabinger Viscometer) and compared results with FPS 2000 (Parker Kittiwake) sensor. This sensor measures decay length associated with the application with real time temperature and dielectric constant value. The experimental results showed excellent correlation between changes in viscosity measured by both methods. Moreover, a pattern of deterioration for a specific engine oil (SAE 5W30) which is utilized for passenger cars and light duty vehicles was also established. This setup is cost effective, handy and offering required level of accuracy to predict deterioration level in terms of viscosity of deteriorated engine oil.